URGENSI ANGGARAN PENDAPATAN BELANJA DAERAH (APBD) TERHADAP PERENCANAAN PEMBANGUNAN DAERAH - Yuliastati, Yuliastati (Katalogis, 2017)
The research was to identify whether or not the provincial development could create people welfare and prosperity through provincial budgets and how the control over the provincial budgets. It was a normative research. The resultsÂ  of the research showed that in planning the provincial development programs using the provincial budgets, the provincial government still needed grass root aspirations in order to secure the provincial developments were consistent with the people expectations in accordance with the potencies in the province.